Reproductive performance and fertility in male and female adult mice chronically treated with hexarelin - Puechagut, Patricia Beatriz (2011)
Hexarelin (HEXr), a synthetic ghrelin analogue, has been associated with modifications of reproductive physiology. In previous studies of adult mice, we detected that HEXr induced significantly reduced ovulation rate and significant correlation coefficients between sexual maturation and corporal weight in offspring. In this study, we investigated the effects of chronic HEXr administration on sperm concentration and functional activity, oestrous cyclicity and pregnancy index, in addition to the number of fetuses and its correlation with the number of corpora lutea. Adult Albino swiss mice were injected (sc) daily with HEXr: 100 mgkg 1 day 1 (HEXr D1) or 200 mgkg 1 day 1 (HEXr D2) for 53 days in males and 30 days in females.We detected a significantly decreased ratio in the number of fetuses per corpora lutea in females treated with HEXr D2 for 30 days before mating and during the first 6 days of pregnancy, in addition to a downward trend in the pregnancy index and percentage of females impregnated by each male treated with both doses of the analogue. Although we did not find any significant effect on additional parameters evaluated in both genders, we propose certain effects of HEXr on the implantation process and/or early development of embryos and over the in vivo reproductive capability of males.